Zeolite-Magnetite Composites to Remove Hg2+ from Water - Pizarro-Arriagada, C; Pizarro-Arriagada, C (Springer International Publishing, 2019)
It is reported an innovative though still exploratory study devoted to characterizing their structure and evaluating the response of zeolite-magnetite composites as adsorbing materials to remove Hg2+ from water. The zeolite material collected from a sampling site in Parral, Chile, was identified and structurally characterized as containing mordenite with crystallographic orthorhombic unit cell dimensions a = 18.060(1) Å; b = 20.429(2) Å and c = 7.5091(7) Å. From Mössbauer data, two paramagnetic ferric iron sites occur in its structure. This zeolite, a sample of synthetic magnetite and their two-component composites were used as adsorbers to sequester Hg2+ dissolved in water. The adsorption rate was found to reach a steady state of nearly constant Hg concentrations corresponding to 26.2; 22.1; 20.6; 17.4 and 16.7 mg Hg per g adsorber, between 24 h and 72 h reaction, for the samples zeolite only, for the composites zeolite:magnetite mass ratio 10:1; 5:1; 1:1 and for the magnetite only, respectively. These corresponding maximum adsorption capacities reduced the initial concentration of Hg2+ in water from 700 mg L−1 to an equilibrium concentration of 0; 110; 150; 240 and 250 mg L−1, respectively. Although the composites showed a lower adsorption capacity of Hg than did the sole zeolite (zeol sample), the composites contained magnetic particles, which allow the adsorbing systems to be readily removed from the aqueous medium, with a magnetic field. These combined characteristic point to the remarkable potential of such materials, particularly the mag-zeol-2, to be used to remediate natural bodies of water contaminated with Hg. © 2019, Springer Nature Switzerland AG.